Anti-β2-glycoprotein I IgG antibodies from 1-year-old healthy children born to mothers with systemic autoimmune diseases preferentially target domain 4/5: might it be the reason for their 'innocent' profile?. Issue 2 (21st October 2010) - Andreoli, Laura; Nalli, Cecilia; Motta, Mario; Norman, Gary L; Shums, Zakera; Encabo, Susan; Binder, Walter L; Nuzzo, Monica; Frassi, Micol; Lojacono, Andrea; Avcin, Tadej; Meroni, Pier-Luigi; et al.
Abstract : Background: Anti-β2 -glycoprotein-I (anti-β2 GPI) were demonstrated to be pathogenic in the antiphospholipid syndrome (APS). However, they can be detected in patients with no features of APS, especially those affected by systemic autoimmune diseases (SAD), and so in healthy children. It has been suggested that anti-β2 GPI against domain 1 (D1) associate with thrombosis, while those recognising domain 4/5 (D4/5) are present in non-thrombotic conditions. Objective: To evaluate the fine specificity of anti-β2 GPI in adults and infants. Methods: Three groups were examined—group A: 57 1-year-old healthy children born to mothers with SAD; group B: 33 children with atopic dermatitis; group C: 64 patients with APS. Subjects were selected based on positive anti-β2 GPI IgG results. Serum samples were tested for anti-β2 GPI IgG D1 and D4/5 using research ELISAs containing recombinant β2 GPI domain antigens. Results: Children (A and B) displayed preferential IgG reactivity for D4/5, whereas patients with APS were mainly positive for D1. No thrombotic events were recorded in groups A and B. Conclusions: The specificity for D4/5 suggests that anti-β2GPI IgG production in children born to mothers with SAD is a process neither linked to systemic autoimmunity nor related to the maternal autoantibody status. This unusual fine specificity might, at least partially, account for the 'innocent' profile of such antibodies.